1975
DOI: 10.1001/archneur.1975.00490540042005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Aneurysms

Abstract: The fine structure of five cerebral aneurysms, four early aneurysmal changes, and three arteriovenous aneurysms (two cerebral and one spinal) were investigated from surgical and autopsy specimens. Each lesion was characterized by thickening, lamination, redundancy, and separation of basement membranes, abundant cellular debris, and a paucity or absence of elastica. In several instances, extracellular lipid and lipophages were present. These vascular lesions were remarkably similar to one another and also to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Thus, the term congenital aneurysm to describe aneurysms in children should probably be abandoned, and the identification of an aneurysm in a child should rather raise the suspicion of an underlying disease affecting the blood vessel wall. A review of published histopathology reports of intracranial aneurysms led to the conclusion that a combination of intraluminal, mural, and extravascular factors are likely responsible for the development of saccular aneurysms [24,25]. Lasjaunias and colleagues [15] suggested that aneurysms in children must be the expression of various vessel wall dysfunctions producing transient or permanent failure to repair a partial insult.…”
Section: Etiology Of Aneurysms In Childrenmentioning
confidence: 99%
“…Thus, the term congenital aneurysm to describe aneurysms in children should probably be abandoned, and the identification of an aneurysm in a child should rather raise the suspicion of an underlying disease affecting the blood vessel wall. A review of published histopathology reports of intracranial aneurysms led to the conclusion that a combination of intraluminal, mural, and extravascular factors are likely responsible for the development of saccular aneurysms [24,25]. Lasjaunias and colleagues [15] suggested that aneurysms in children must be the expression of various vessel wall dysfunctions producing transient or permanent failure to repair a partial insult.…”
Section: Etiology Of Aneurysms In Childrenmentioning
confidence: 99%
“…The supposed mechanism of enlargement is the laminar necrosis, thrombus formation within the aneurysm followed by scarring of the wall or repeated small haemorrhages which are subjected to the process of encapsulation and organisation. The ultrastructure of aneurysms has been extensively studied (90,134,143). In children giant aneurysms may show a thin wall without any fibrotic thickening (19).…”
Section: Aetiology Pathology and Mechanism Of Growthmentioning
confidence: 99%
“…Some measurements of the macroscopic mechanical properties of cerebral arteries and aneurysms exist (Coulson et al, 2004;Monson et al, 2003Monson et al, , 2005Scott et al, 1972;Steiger, 1990;Tóth et al, 1998Tóth et al, , 2005 and the structural organisation of these tissues is fairly well documented (Canham et al, 1991b(Canham et al, ,a, 1992(Canham et al, , 1996(Canham et al, , 1999Finlay et al, 1991Finlay et al, , 1995Finlay et al, , 1998Hassler, 1972;MacDonald et al, 2000;Rowe et al, 2003;Smith et al, 1981;Whittaker et al, 1988). In the aneurysmal wall, the tunica media and the internal elastic lamina have often disappeared or are severely fragmented (Abruzzo et al, 1998;Sakaki et al, 1997;Stehbens, 1963;Suzuki and Ohara, 1978;Tóth et al, 1998). In either case, these layers do not seem to contribute significantly to the structural integrity of the aneurysmal wall.…”
Section: Introductionmentioning
confidence: 99%